Training whilst under quarantine - Gooden, J. (University of Cambridge, 2020)
As you might expect, demand for home-based training equipment is through the roof at the moment. If you were able to get your hands on some equipment in recent weeks, you are one of the lucky ones! Not everyone has been so fortunate but don't worry, you can find a plethora of home-based workouts to complete at home. However, some of them just don`t cut it, perhaps you`ve done bodyweight exercises to death and cannot wait to get back to the addition of using weights again. If this is the case, or perhaps you want some new exercise ideas, check out the content below.